2018
DOI: 10.1016/j.cmi.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Is biofilm production a prognostic marker in adults with candidaemia?

Abstract: Biofilm production was not a predictor of mortality or of unfavourable prognosis in adults with candidaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…Studies using biofilm mass as predictor of mortality reported similarly versatile results; Muñoz et al (2018) and Shin et al (2002) did not find biofilm development, as determined by a crystal violet or safranin‐related assay, to be associated with increased mortality . However, the latter study involved a large proportion of C parapsilosis isolates, which are generally associated with low mortality .…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Studies using biofilm mass as predictor of mortality reported similarly versatile results; Muñoz et al (2018) and Shin et al (2002) did not find biofilm development, as determined by a crystal violet or safranin‐related assay, to be associated with increased mortality . However, the latter study involved a large proportion of C parapsilosis isolates, which are generally associated with low mortality .…”
Section: Discussionmentioning
confidence: 53%
“…Based on a recent epidemiological meta‐analysis, the incidence of candidaemia in Europe is 3.88 cases per 100 000 corresponding to approximately 79 cases per day . According to a number of studies, patients infected by biofilm‐producing isolates have a worse prognosis; however, contradicting studies also exist . This controversy is probably due, at least partly, to variability in the cut‐off values used to distinguish low from intermediate and high biofilm producers The other possible reason may be the high variability of the examined patient populations …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations